Nikolai Fedorovich Gamaliya (1932–2016) (Experimental Oncology, 2016)
Professor Nikolai Fedorovich Gamaliya, well-known scientist in the field of laser biomedical research, biophysicist, authority in experimental oncology, Laureate of the State Prize in Science and Techno logy of Ukraine, Head of the Department of Biological Effects of Ionizing and Non-Ionizing Radiation of R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the National Academy of Sciences (NAS) of Ukraine died on June 14, 2016 at the age of 83.